An Innovative Management Model for Early Childhood Education Learning Based on a Culture of Self-Reliance in the Digital Era - Aisyah, Eny Nur; Arifin, Imron; Putra, Yudithia Dian; Tirtaningsih, Munaisra Tri; Kustiawan, Usep; Huwaina, Nurrul (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2026)
This study aims to develop and analyse an innovative management model for early childhood learning grounded in local culture, leveraging digital technology. The research focuses on developing a learning management system integrated with the values of cultural wisdom “Kedirian” through an interactive digital storytelling application. The approach used is research and development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Data were collected through observation, interviews, and pre- and post-tests. The results of the study indicate that implementing this innovative management model significantly increases children’s active participation, strengthens their understanding of character values, including honesty, cooperation, and patience, and develops their socio-emotional skills in early childhood. The main product of this research is the Dongeng Digital Nusantara Kediri application, which uses Generative AI to present local fairy tales such as the Legend of Mount Kelud and Calon Arang in interactive visual and audio formats. These findings emphasise the importance of integrating technology and culture in early childhood learning management to shape a young generation with character, rooted in local culture, in the digital era.